MADRASAH PRINCIPAL SUPERVISION IN DEVELOPING TEACHERS' SOCIAL COMPETENCE - Rahmatillah, Alda Novita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research focuses on the efforts to enhance the social competence of teachers carried out by the school principal through their role as a supervisor. Through supervisory activities, the school principal can assist employees and teachers through guidance, mentoring, and job improvement, which can enhance the social competence of teachers. The study utilizes a qualitative descriptive phenomenology method with a literature review approach (library research). The results of this research explain that teachers need to possess competencies, including pedagogical competence, personality competence, social competence, and professional competence. One of these competencies is social competence. Social competence means that teachers must have the ability to engage in social communication with students, fellow teachers, school principals, and the community, especially with students, to be effective in the implementation of the teaching and learning process